Design of an unmanned ground vehicle 2 - Hong, Yong Chun (2016)
There has been a growing trend in the usage of Unmanned Ground Vehicle across the world. It can be seen highly used in both the military and civilian life to perform human’s duty. Especially in the military, it is used to replace the human in all the dangerous activities so that life will not be loss. The usage of Unmanned Ground Vehicle can be dated back to early 1930s where the first UGV was created for military use.